2012
DOI: 10.1016/j.cub.2011.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and Central Inputs Shape Network Dynamics in the Developing Visual Cortex In Vivo

Abstract: Spontaneous network activity constitutes a central theme during the development of neuronal circuitry [1, 2]. Before the onset of vision, retinal neurons generate waves of spontaneous activity that are relayed along the ascending visual pathway [3, 4] and shape activity patterns in these regions [5, 6]. The spatiotemporal nature of retinal waves is required to establish precise functional maps in higher visual areas, and their disruption results in enlarged axonal projection areas (e.g., [7-10]). However, how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
203
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(219 citation statements)
references
References 35 publications
(50 reference statements)
14
203
2
Order By: Relevance
“…across primary sensory areas in vitro and in vivo and during conditions of sensory deprivation (Golshani et al 2009;Rochefort et al 2009;Siegel et al 2012), with the same postnatal time course. The ubiquity and generality of this trajectory suggest a strong, internally mediated mechanism for patterning spontaneous activity during the development of primary sensory neocortical areas, regardless of the sensory experience of the cortical area during this developmental period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…across primary sensory areas in vitro and in vivo and during conditions of sensory deprivation (Golshani et al 2009;Rochefort et al 2009;Siegel et al 2012), with the same postnatal time course. The ubiquity and generality of this trajectory suggest a strong, internally mediated mechanism for patterning spontaneous activity during the development of primary sensory neocortical areas, regardless of the sensory experience of the cortical area during this developmental period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in vivo has shown that within layer 2/3 neurons synchronous activity transitions to sparse activity around the time of eye opening at the beginning of the third postnatal week in primary visual cortex (Siegel et al 2012). The timing of this change suggests that sensory input is necessary.…”
mentioning
confidence: 92%
“…Also, grafted neural stem cells exhibit spontaneous Ca 2+ activity that depends on gap junctions (38). Moreover, different patterns of spontaneous activity has been reported in regions of the developing visual cortex (39), and amplitude and frequency of Ca 2+ oscillations were correlated positively with the rate of neuronal migration (25,26). Our findings show that the spontaneous Ca 2+ activities in each cell are not uncorrelated, independent cell signals, but rather highly ordered signaling events creating small-world networks that follow a scalefree topology.…”
Section: Spontaneous Camentioning
confidence: 99%
“…Although most studies have been performed in vitro, these findings have also been validated in vivo (Ackman et al 2012;Siegel et al 2012). The spatiotemporal features encoded in the waves are hypothesized to provide cues for the establishment of retinal receptive fields (Sernagor et al 2001), as well as for eye-specific ON-OFF pathway segregation and visual map formation in retinal targets (Wong & Oakley, 1996;Wong, 1999;Lee et al 2002;Akrouh & Kerschensteiner, 2013).…”
Section: Introductionmentioning
confidence: 99%